2020
DOI: 10.3390/cancers12082279
|View full text |Cite
|
Sign up to set email alerts
|

Actively Targeted Nanodelivery of Echinomycin Induces Autophagy-Mediated Death in Chemoresistant Pancreatic Cancer In Vivo

Abstract: Pancreatic cancer remains a recalcitrant neoplasm associated with chemoresistance and high fatality. Because it is frequently resistant to apoptosis, exploiting autophagic cell death could offer a new treatment approach. We repurpose echinomycin, an antibiotic encapsulated within a syndecan-1 actively targeted nanoparticle, for treatment of pancreatic cancer. Tumor-specific uptake, biodistribution, efficacy of nanodelivered echinomycin, and mechanism of cell death were assessed in aggressive, metastatic models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 64 publications
1
6
0
Order By: Relevance
“…negative effects of Quinomycin A, a recent study showed that actively targeted nano-delivery of Quinomycin A can efficiently target cancer cells to induce autophagic cell death instead of apoptosis or necrotic cell death. 40 In our studies, we found that ADPKD cells lose significant viability at a higher dose of 10 nmol/L Quinomycin A whereas, NHK cells retain their viability. Our in vitro studies also indicated that Quinomycin A specifically targeted cystic epithelial cells for apoptosis.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…negative effects of Quinomycin A, a recent study showed that actively targeted nano-delivery of Quinomycin A can efficiently target cancer cells to induce autophagic cell death instead of apoptosis or necrotic cell death. 40 In our studies, we found that ADPKD cells lose significant viability at a higher dose of 10 nmol/L Quinomycin A whereas, NHK cells retain their viability. Our in vitro studies also indicated that Quinomycin A specifically targeted cystic epithelial cells for apoptosis.…”
Section: Discussionsupporting
confidence: 46%
“…Recent studies in mice indicate that low doses (eg, 10 μg/kg body weight) of Quinomycin A are not toxic to normal cell hematopoiesis and selectively targets cancerous cells in acute myelocytic leukemia and bladder cancer 13,14 . To further combat the negative effects of Quinomycin A, a recent study showed that actively targeted nano‐delivery of Quinomycin A can efficiently target cancer cells to induce autophagic cell death instead of apoptosis or necrotic cell death 40 . In our studies, we found that ADPKD cells lose significant viability at a higher dose of 10 nmol/L Quinomycin A whereas, NHK cells retain their viability.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, while in vitro ACF treatment reduced hypoxia-induced overexpression of PGK-1 and VEGF in glioma cell lines, in vivo treatments with different ACF/polymer ratios in a preclinical model led to high survival rates in rats with gliosarcoma [161]. Echinomycin, another well-known direct HIF inhibitor, hampers the binding of HIF1α to the HRE sequence in the VEGF promoter [162], and a recent study by Thomas and collaborators (2005) has demonstrated that nano-delivery of echinomycin induces autophagy-mediated death in pancreatic cancer in vivo, wherein syndecan-1-encapsulated echinomycin, a custom-designed tumor-specific delivery method, resulted in significantly greater survival [163].…”
Section: Targeting Hif-mediated Angiogenesis: a Pharmacological Approachmentioning
confidence: 99%
“…Large payloads delivered to the tumor as a result of the EPR effect leads to improved drug efficacy while minimizing off-target delivery and damage [ 46 ]. Further, surface modifications allow for active-targeting of tumor features, such as folate receptor [ 47 ] or syndecan-1 [ 48 ], for improvement over the EPR effect. Coating of liposomes with other materials, such as polymers (see below), have been investigated to further increase specificity to cancer.…”
Section: Strategies Of Constructing Nanotheranosticsmentioning
confidence: 99%